Canoe country wildlife : a field guide to the North Woods and Boundary Waters - Stensaas, Mark (University of Minnesota Press, 2004)
Canoe Country Wildlife, a friendly field guide, introduces the wildlife most seen travel in the North Woods. It describes these creatures and their habits.